BIOPROSPECTING OF INDIGENOUS MYXOBACTERIA ISOLATED FROM SOIL AND DECAYING WOOD IN TOBA-SAMOSIR, NORTH SUMATERA AS ANTIMICROBIAL PRODUCER - Siti Meliah (BERITA BIOLOGI, 2022)
Gram-negative myxobacteria is a member of Deltaproteobacteria with some unique characteristics including move by gliding motility, form fruiting bodies when starving, and prey on other microorganisms. They are known to produce some of the potential and novel antimicrobial compounds. Therefore, in this study we aim to isolate and screen indigenous myxobacteria as an attempt to bioprospect their potential as antimicrobial substances producer. Samples consist of soils, plant rhizospheres, and decaying woods collected from Toba-Samosir, North Sumatera were subjected to isolation procedure using baiting and filter membrane methods. A total of 23 isolates visually displaying myxobacteria features were selected and molecularly identified. Analysis on their 16S rRNA gene sequences resulted in grouping them in the genus Corallococcus, Cystobacter, and Myxococcus. Antimicrobial assay using agar plug diffusion method revealed that they were able to inhibit the growth of Candida albicans. Some of the highest inhibition zones were produced by Cystobacter velatus isolates, hence indicating their potential as anti-Candida compound producer.